Programa de mantenimiento preventivo del parque de máquinas y equipos de la empresa FAMECA SAC. - Mendoza Aroca, Juan Carlos (2019)
This project is carried out with the purpose of establishing a preventive maintenance proposal for the company's machines and equipment, to improve its management rates. The program design is established based on the theory and strategies that meet the requirements. The project begins with a summary information on the importance, procedures and uses of data obtained in advance. Subsequently, advantages and disadvantages are pointed out over the different types of maintenance alternatives, in order to, by means of an analysis, choose the most appropriate strategy to achieve the established objectives. From the selected alternative, the final disposition and selection of the appropriate option are detailed. Finally, the project will conclude with the design of the most appropriate maintenance plan and ends with the determination of the approximate costs for compliance with it.